Художня трансформація фольклорних мотивів і образів в українській літературі першої половини ХІХ ст. - Коломієць, В.; Іванова, О. (Народна творчість та етнографія, 2006)
Here was given a review of the important problem of study of literature science - artistic transformation of folklore motives and characters in Ukrainian literature of the first part of XIX century, especially in works of H. Skovoroda, I. Kotlyarevskiy, P. Hulak-Artemovskiy, G. Kvitka-Osnov'yanenko, E. Grebinka and others. The author underlines that in aesthetics of Ukrainian writers of mentioned period the question of artistic mastering of folklore was of personage characters, folklore helped them to see typical features and important events of those times.